N-Butyllithium-mediated synthesis of N-aryl tertiary amines by reactions of fluoroarenes with secondary amines at room temperature. Issue 11 (16th March 2017) - Lin, Yingyin; Li, Meng; Ji, Xinfei; Wu, Jingjing; Cao, Song
Abstract: A simple and facile method for the synthesis of aromatic tertiary amines by amination of fluoroarenes with secondary amines in the presence of n -butyllithium at room temperature was reported. Graphical abstract: